Combined effect of new generation herbicides on weed population, soil microbial population and yield in direct seeded rice (Oryza sativa L.) - Suganya, R; Sanjay, D J; Suresh, K S M; Baradhan, G (Plant Science Today, 2025)
Weeds are considered the biggest threat to direct seeded rice (DSR) which must be managed effectively to augment yield and economics in DSR. Hence, field experiments were conducted at Periyanarkunam, Bhuvanagiri taluk, Tamil Nadu. The studies comprised one preliminary field experiment conducted during Navarai 2021 to identify a suitable direct-seeded rice establishment method. The trial was laid in a split plot design with three main treatments (dry seeded, drum seeded and manual wet seeded rice) and nine sub treatments consisting of different weed management methods. In addition, two main field experiments during Kuruvai 2021 and 2022 to evaluate the impact of new generation herbicidal combinations on weed population, soil microbial population and yield in direct-seeded rice. These experiments followed a randomized block design with six weed management practices and four replications. The result showed that among the establishment methods drum seeded rice recorded the highest yield, which was comparable with manual wet seeded rice (M3). However, in term of economics drum seeded rice documented the highest benefit-cost ratio (2.22) compared to manual wet seeded rice (1.95). Regarding weed management practices, application of new generation herbicides at a low dose did not show any detrimental effect on soil microbial population. Among the treatments tested, bensulfuron methyl 0.6 % + pretilachlor 6 % granules at 10 kg ha-1 application on 8 DAS (days after sowing) as pre-emergence (PE) followed by metsulfuron methyl 10 % + chlorimuron ethyl 10 % at 20 g ha-1 application on 25 DAS as postemergence (PoE) and followed by hand weeding at 45 DAS, recorded the lowest weed population, the highest weed control efficiency and superior yield across all experiments. Hence, this practice is both efficient weed management and economically feasible for effective control of weeds in direct seeded rice.